PERAN GURU DALAM MEMBENTUK ADAB SISWA DALAM MANAJEMEN PENDIDIKAN ISLAM - Hidayat, Alfian (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
Discussions about education in today's era focus on learning and education not only on how students learn basic science and knowledge about the subjects they study, but problems regarding etiquette, behavior, manners, morals, etiquette are also a highlight that needs to be emphasized. Research This aims to form adab for students in improving the quality of Islamic education in Islamic education management. This study uses a qualitative research method, which in this study uses the library research method. The findings in the literature research show that ethics and morals are two components that every student must have. Even in the literature described, a teacher is required to have good ethics in the process of teaching and learning activities. learning process. One of the leading scholars Imam Ibn Qayyim rahimahullah said that,